2021
DOI: 10.1088/1361-6471/abc864
|View full text |Cite
|
Sign up to set email alerts
|

Critical properties of symmetric nuclear matter in low-density regime using effective-relativistic mean field formalism

Abstract: The effective field theory motivated relativistic mean-field (E-RMF) formalism is employed to study the equation of state (EoS) for the infinite symmetric nuclear matter (SNM) at finite temperature using the recently developed forces FSUGarnet, IOPB-I, G3, and the well known NL3 force parameter. The EoS is then used to estimate the critical temperature T c, pressure P c and density ρ c of the SNM for the liquid–gas phase transition. As T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…This formalism has been applied in a wide range of nuclear physics problems in the past few years [59][60][61][62][63][64]. The E-RMF effective Lagrangian which include the interaction between different mesons, such as, σ, ω, ρ, δ and photon is written as [47,50,[65][66][67][68],…”
Section: B Effective Relativistic Mean-field Theorymentioning
confidence: 99%
“…This formalism has been applied in a wide range of nuclear physics problems in the past few years [59][60][61][62][63][64]. The E-RMF effective Lagrangian which include the interaction between different mesons, such as, σ, ω, ρ, δ and photon is written as [47,50,[65][66][67][68],…”
Section: B Effective Relativistic Mean-field Theorymentioning
confidence: 99%
“…Thus discontinuity in density suggests the transition from one layer of the nucleus to another. One also gets rid of the Maxwell construction [60] to determine the transition pressure from one nucleus to another. The pressure can be calculated from the first law of thermodynamics as [49]…”
Section: A Outer Crustmentioning
confidence: 99%
“…In this case, the interaction between different mesons, such as, σ, ω, ρ and δ is included up to fourth order. The photon field is also included with E-RMF energy density functional as [29,54,60,[64][65][66]…”
Section: Effective Relativistic Mean-field Theorymentioning
confidence: 99%
“…6 MeV for the mass region A ≈ 90 in ALADIN experiment [11]. Nuclear multi-fragmentation occurs in the region of spinodal or phase instability boundary in the nuclear matter phase diagram [12]. The nucleus, which resembles a hot liquid drop, expands because of thermal pressure and moves to the spinodal region where it is surrounded by a nucleon gas.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature-dependent surface energy term depends on the T c which is calculated for these individual E-RMF parameter sets. In the analysis of critical properties of infinite nuclear matter using these E-RMF sets in [12], we found that the T c is not a well-constrained quantity and the majority of E-RMF sets that satisfy the relevant observational and experimental constraints on EoS underestimates it. Since the experimental value of T c is calculated by extrapolating the data from multifragmentation reaction data on finite nuclei, it is interesting to see the variation of T l of finite nuclei using different E-RMF forces.…”
Section: Introductionmentioning
confidence: 99%